BIOSIS today - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
BIOSIS is the producer of the world's largest . biological and biomedical database, dedicated to providing the international life science community with continuing and comprehensive research information. The organization has now been operative for...